Workflow issues of Hospital Information Management Systems in Pakistan - Qasim, Syed Shahzaib; Ziaei Nafchi, Majid; Sudzina, František; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2023)
The Health Information Management System (HIMS) was created to produce data on the status of ongoing health-related activities in order to support effective management of health care systems at all levels and decision-making based on evidence. This term has been the center of attention in healthcare department since the start of 21st century and has been discussed in literature several times. In Pakistan, this technology is new and many hospitals face workflow issues after the deployment of HIMS. The goal of this study is to analyze these issues along with some static issues that hamper the integration of technology in healthcare. Moreover, some solutions are also provided to curb these issues. The experimental results show the presence of workflow issues in both public and private hospitals. These results are obtained after e-mail surveying. However, if the recommendations which are suggested, are adopted these issues can be resolved.
Vedoucí práce: Majid Ziaei Nafchi
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: information systems management [obor dipl. práce]; diplomové práce; master's theses